Lysine succinylation and SIRT5 couple nutritional status to glutamine catabolism - Michael J. Lukey; Kai Su Greene; Richard A. Cerione (Molecular & Cellular Oncology, 2020)
The metabolic microenvironment of tumors is characterized by fluctuating and limited nutrient availability. To survive these conditions, cancer cell-intrinsic mechanisms sense and signal nutritional status. We describe how glutaminase (GLS) is destabilized by lysine succinylation and stabilized by the NAD+-dependent desuccinylase sirtuin 5 (SIRT5), coupling nutrient levels to metabolic flux.